Emerging Roles for von Willebrand Factor in Cancer Cell Biology - O'Sullivan, Jamie M.; Preston, Roger J. S.; Robson, Tracy; O'Donnell, James S. (Seminars in Thrombosis and Hemostasis, 2018)
von Willebrand factor (VWF) is a complex multimeric plasma glycoprotein that plays critical roles in normal hemostasis. However, additional novel roles for VWF in modulating cancer cell biology, and in particular tumor metastasis, have recently been reported. Markedly elevated plasma VWF levels were associated with advanced tumor stage and metastatic disease. These observations have raised the question of whether VWF may be involved in regulating tumor progression. Interestingly, novel findings indicate that VWF is expressed by a variety of tumor cells of nonendothelial origin. Critically, tumor cells that exhibit de novo acquired VWF expression demonstrate enhanced binding to endothelial cells (EC) and platelets, and increased extravasation through EC barriers. Furthermore, in vitro studies have shown that VWF can bind a variety of different tumor cells mediated by specific receptors expressed on the tumor cell surface. The concept that VWF is important in modulating tumor metastasis is further supported by in vivo experiments demonstrating that antibody-mediated VWF inhibition significantly attenuated murine metastasis. Intriguingly, however, VWF binding to specific human tumor cell lines results in apoptosis. In this study, the authors provide an overview of recent advances supporting a role for VWF in regulating multiple aspects of cancer cell biology.
Keywords: von Willebrand factor; cancer; metastasis